Evaluation of the safety and potential lipid-lowering effects of oral hydrogen-rich coral calcium (HRCC) capsules in patients with metabolic syndrome: a prospective case series study - Chiu, Szu-Han; Douglas, Frank L.; Chung, Jia-Ru; Wang, Kuang-Yih; Chu, Chao-Fang; Chou, Hsia-Yun; Huang, Wei-Chih; Wang, Tian-Yu; Chen, Wen-Wen; Shen, Min-Chung; Liu, Feng-Cheng; Hsiao, Po-Jen (Frontiers in Nutrition, 2023)
Background Metabolic syndrome is characterized by a cluster-like occurrence of conditions such as hypertension, hyperglycaemia, elevated low-density lipoprotein (LDL) cholesterol or triglycerides (TG) and high visceral fat. Metabolic syndrome is linked to the build-up of plaque within the artery, which leads to disorders of the circulatory, nervous and immune systems. A variety of treatments target the regulation of these conditions; nevertheless, they remain dominant risk factors for the development of type 2 diabetes (T2DM) and cardiovascular disease (CVD), which affect 26.9% of the US population. Management and intervention strategies for improving cholesterol and/or TG are worthwhile, and recent studies on hydrogen treatment are promising, particularly as molecular hydrogen is easily ingested. This study aimed to investigate the lipid-lowering effects and quality of life (QOL) improvement of hydrogen-rich coral calcium (HRCC) in patients with metabolic syndrome. Methods The patients, all Taiwanese, were randomly assigned to 3 different doses (low, medium, and high) of HRCC capsules. The primary outcome was the adverse effects/symptoms during this 4-week use of HRCC capsules. The secondary outcome was lipid profile changes. Complete blood count, inflammatory biomarkers, and QOL were also measured before and after the course of HRCC. Results Sixteen patients with metabolic syndrome completed this study (7 males, 9 females; mean age: 62 years; range: 32–80). No obvious adverse effects were recorded. Only changes in blood TG reached significance. The baseline TG value was 193.19 µL (SD = 107.44), which decreased to 151.75 µL (SD = 45.27) after 4 weeks of HRCC (p = 0.04). QOL showed no significant changes. Conclusions This study is the first human clinical trial evaluating HRCC capsules in patients with metabolic syndrome. Based on the safety and potential TG-lowering effects of short-term HRCC, further long-term investigations of HRCC are warranted.